Enzymatic hydrolysis of insect Alphitobius diaperinus towards the development of bioactive peptide hydrolysates - Sousa, Pedro (2020)
Edible insects are a promising protein source for the future generation, due to their nutritional composition, sustainability and low environmental impact. Recent studies demonstrated their potential as a protein base to obtain bioactive peptides with potential applicability in the food industry. The aim of this study was to hydrolyze and analyze the potential of the edible insect Alphitobius diaperinus protein to develop an improved insect food ingredient with bioactive properties. After evaluating various conditions for the enzymatic hydrolysis with Alcalase 2.5L and Corolase PP, the best condition chosen for each enzyme was an enzyme : substrate ratio of 1.5% for 4 hours and a ratio of 3.0% for 6 hours, respectively. Insect protein hydrolysates are demonstrated to have relevant bioactive properties, namely antioxidant (by ABTS and ORAC methods) and antihypertensive activities (through the ability to inhibit the angiotensin converting enzyme, ACE), but no antimicrobial or antidiabetic properties were observed. Antioxidant activity values for hydrolysates obtained with Alcalase 2.5L and Corolase PP were 95.0 ± 0.8 and 95.7 ± 1.0 μmol Trolox equivalent per g insect powder by the ABTS method, 825.6 ± 85.5 and 944.8 ± 68.1 μmol Trolox equivalent per g insect powder by the ORAC method, respectively. Insect hydrolysates were able to inhibit the ACE and IC50 values for insect hydrolysates obtained with Alcalase 2.5L and Corolase PP were 55.5 ± 6.2 and 107.4 ± 9.7 μg of protein per mL, respectively. These insect protein hydrolysates can be used as a supplement/ingredient in the food industry with potential health benefits.